Moxonidine in combined therapy of essential arterial hypertension patients with chronic obstructive pulmonary disease - N. R. Paleev; E. G. Shuganov; N. A. Raspopina; N. V. Vilchinskaja (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To study moxonidine and calcium antagonist (amlodipine) effectiveness in essential arterial hypertension (EAH) treatment among patients with chronic obstructive pulmonary disease (COPD), and therapy effects on concomitant dyslipidemia. Material and methods. In total, 30 patients with EAH and Stage 2-3 COPD, aged 39-70 years, were examined. Antihypertensive therapy was started by amlodipine, in the dose of 5 mg/d, increasing up to 10 mg/d 7-10 days later, if target blood pressure (BP) level wasn’t achieved. If target BP figures were not achieved after three-week treatment, moxonidine (0.2-0.4 mg/d) was added. Treatment effectiveness was assessed by spirometry, 24-hour peak flowmetry, 24-hour BP monitoring, lipid profile (LP), glucose and uric acids level assessment. Results. In 16 COPD and EAH patients, BP was normalized in amlodipine monotherapy (5-10 mg/d); in 14 patients – after adding moxonidine (0.4 mg/d). At Week 6 of the combined therapy, LP improved substantially, with blood glucose, uric acid levels and bronchial conductivity remaining the same. Conclusion. To achieve target BP levels in COPD and EAH patients, the combination of amlodipine (10 mg/d) and moxonidine (0.2-0.4 mg/d) can be recommended. It provides effective BP control, as well as improves heart rate variability and BP improvement, without affecting lung function, or blood levels of uric acid and glucose.